Zirconia Primers Improve the Shear Bond Strength of Dental Zirconia. Issue 1 (22nd January 2019) - Steiner, René; Heiss‐Kisielewsky, Irene; Schwarz, Vincent; Schnabl, Dagmar; Dumfahrt, Herbert; Laimer, Johannes; Steinmassl, Otto; Steinmassl, Patricia‐Anca
Abstract: Purpose: Various resin cements and priming agents are available for adhesive luting of zirconia restorations. The purpose of this study was to investigate how cement type and priming protocol affect the shear bond strength on zirconia ceramics. Materials and Methods: Yttria‐stabilized tetragonal zirconia polycrystalline ceramic cylinders were bonded to flat zirconia ceramic surfaces using 7 commercially available resin cements. Ten specimens of each cement group were pretreated with a universal primer, and 10 specimens per group were bonded without pretreatment. In addition, 10 specimens per group were pretreated with system‐specific zirconia primers, which were available for 3 cements. Altogether, 170 bonded specimens were water‐stored, thermal‐cycled, and then submitted to shear bond strength tests. The shear bond strength and the fracture types were documented. Differences in shear bond strengths were assessed using 2‐way ANOVA with post‐hoc test (α = 0.05). A point‐biserial correlation was run between the fracture patterns and the shear bond strengths. Results: The mean shear bond strengths of cements in the unprimed group showed large variations between 2.52 ± 3.01 (mean ± SD) MPa and 33.15 ± 7.35 MPa. Pretreating the specimens with a universal primer improved the shear bond strengths significantly in all groups ( p < 0.05) with a range of 21.80 ± 12.51 to 57.20 ± 11.40 MPa. The system‐specific primers also improved the shear bond strength significantly, compared to the unprimed group ( p < 0.01); however, only one system‐specific primer achieved a shear bond strength superior to the universal primer ( p < 0.01). There was also a statistical correlation between the fracture type and the shear bond strength ( p < 0.0005), with cohesively fractured specimens showing higher shear bond strengths (37.24 ± 19.87 MPa) than adhesively fractured specimens (23.10 ± 17.65 MPa) ( p < 0.001). Conclusion: Using universal primer can enhance the maximal shear bond strength of zirconia.